HEDONISM IN EUGENE O NEIL’S: A LONG DAYS JOURNEY INTO NIGHT (Lembaga Pengembangan Kinerja Dosen, 2022)
The objective of this study is to investigate Hedonism in the Eugene O’ Neil’s drama A Long Days Journey Into Night. This study uses descriptive qualitative to explore the kind of hedonism on the dialogue utterance of characters in that drama. The results of the data were found that the most frequent types was folk hedonism 24%, value hedonism 10%, motivational hedonism 22%, normative hedonism 16%, egoist hedonism 14% and Utilitarian hedonism 14%. Folk hedonism occurs in the character named James Tyrone because he seeks his own pleasure without thinking about what will happen in the future. Value hedonism occurs in a character named Mary Tyrone, who at that time was looking for her pleasure which she thought was valuable in her life. The motivation states that hedonism was created on the basis of the human desire to relieve the pain experienced by a character named Edmund Tyrone. Normative hedonism was carried out by a character named Mary Tyrone, who at that time was looking for fun as it should be. Egoist hedonism is carried out by characters named James Tyrone and Jamie Tyrone, at that time they were doing pleasure at the expense of others. Utilitarian hedonism was carried out by characters named Mary Tyrone and Edmund Tyrone who at that time were also looking for fun for their families not only for themselves. The final conclusion is folk hedonism is a very dominating problem in the lives of the characters in Eugene O'Neil's drama A Long Days Journey Into Night in accordance with today's life, because humans prefer to seek pleasure but forget the impact that will be obtained in the future.